Focal Adhesion Kinase Related Gynecologic Cancer: a review - Duangmani Thanapprapasr (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Gynecologic cancer is a major health burden in women across the world. Almost a half million mortalities from gynecologic cancer were reported every year. Knowledge in molecular biology research on cancer could lead to develope novel therapeutic options in gynecologic cancer. Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase which plays an essential role in cancer cells survival, migration, invasion, metastasis and also tumor angiogenesis. Various human cancerous tissues were demonstrated over expression of FAK which were correlated to the survival. There were evidences showed that FAK involved in molecular pathways of ovarian cancer, endometrial cancer and cervical cancer. In the light of this review, FAK has been a promising mediator that regulates cancer growth and metastasis. Therefore, molecular therapies targeted FAK may be beneficial for patients with gynecologic cancer in the near future.